Long Memory and Stock Market Efficiency: Case of Saudi Arabia - Lamouchi, Rim Ammar (International Journal of Economics and Financial Issues, 2020)
This paper examines the market efficiency of Saudi Arabia stock exchange market namely Tadawul All Share Index, TASI, for the period from 1998 to 2020. To test the efficiency of stock market, we analyze the dependence structure of stock market index returns and volatility. The results demonstrate that Saudi stock market shows long memory. The long memory process of Saudi Stock Market offers evidence against efficient market hypothesis (EMH). The ARFIMA model supports the presence of long-run dependence in the historical volatility of the Saudi stock market, giving further support against the EMH. Keywords: Market efficiency, Long memory, Stock market Index. JEL Classifications: C13, C22, C53, G10, G17 DOI: https://doi.org/10.32479/ijefi.9568